A reliable analytical procedure to determine the carbon isotopic signature of CO2-bearing COH fluids generated in petrological experiments - L. Toffolo; L. Minopoli; E. Ferrari; S. Tumiati (European Journal of Mineralogy)
The ratio of stable carbon isotopes, δ13C, serves as a fundamental tracer for geological processes. Experiments aiming to replicate isotopic exchange between carbon reservoirs encounter significant analytical challenges due to the limited sample size and issues related to sampling, particularly when dealing with volatile species. Here we present a novel methodology that integrates a capsule-piercing device, a quadrupole mass spectrometer (QMS), and isotopic ratio mass spectrometry (IRMS) to measure the CO2 concentration and natural-like δ13C ratio of CO2 in the volatile COH phase generated in petrological experiments. To validate the technique, we first analyze the COH fluid resulting from the thermal decomposition of 1 mg of anhydrous oxalic acid. The optimal values of the carrier gas flow in the QMS, sampling times, and chromatography column temperature for IRMS are determined. The high degree of similarity, within acceptable errors, observed in both compositional and isotopic analyses indicates a robust reproducibility, minimally affected by contamination and fractionation effects during sampling. We also show that this methodology can be applied for estimating the δ13C of CO2 produced from high-pressure, high-temperature, redox-buffered piston–cylinder experiments. This offers a multitude of opportunities in designing experiments focused on determining isotopic fractionation models for geological processes that involve, but are not restricted to, CO2-bearing COH fluids.